A novel mutation in TTC19 associated with isolated complex III deficiency, cerebellar hypoplasia, and bilateral basal ganglia lesions - Melchionda, Laura; Damseh, Nadirah S.; Abu Libdeh, Bassam Y.; Nasca, Alessia; Elpeleg, Orly; Zanolini, Alice; Ghezzi, Daniele (Frontiers in Genetics, 2014)
Isolated complex III (cIII) deficiency is a rare biochemical finding in mitochondrial disorders, mainly associated with mutations in mitochondrial DNA MTCYB gene, encoding cytochrome b, or in assembly factor genes (BCS1L, TTC19, UQCC2 and LYRM7), whereas mutations in nuclear genes encoding cIII structural subunits are extremely infrequent. We report here a patient, a 9 year old female born from first cousin related parents, with normal development till 18 months when she showed unsteady gait with frequent falling down, cognitive and speech worsening. Her course deteriorated progressively. Brain MRI showed cerebellar vermis hypoplasia and bilateral lentiform nucleus high signal lesions. Now she is bed ridden with tetraparesis and severely impaired cognitive and language functions. Biochemical analysis revealed isolated cIII deficiency in muscle, and impaired respiration in fibroblasts. We identified a novel homozygous rearrangement in TTC19 (c.213_229dup), resulting in frameshift with creation of a premature termination codon (p.Gln77Argfs*30). Western blot analysis demonstrated the absence of TTC19 protein in patient’s fibroblasts, while Blue-Native Gel Electrophoresis analysis revealed the presence of cIII-specific assembly intermediates. Mutations in TTC19 have been rarely associated with mitochondrial disease to date, being described in about ten patients with heterogeneous clinical presentations, ranging from early onset encephalomyopathy to adult forms with cerebellar ataxia. Contrariwise, the biochemical defect was a common hallmark in TTC19 mutant patients, confirming the importance of TTC19 in cIII assembly/stability. Therefore, we suggest extending the TTC19 mutational screening to all patients with cIII deficiency, independently from their phenotypes.